ACTUAL QUESTIONS ABOUT INVESTIGATOR'S WORK IN LATVIAN CRIMINAL PROCEDURE - Sumbarova, Marina (Administrative and Criminal Justice, 2017)
In this article author considers the questions connected with activity of the investigator at investigation of crimes, gives the characteristic of his procedural activity, defines his legal status in Latvian criminal procedure, characterizes important functions that this participant of criminal trial has. Along with consideration of a legal status of the investigator in criminal trial of Latvia, the analysis of the relevant procedural characteristics connected with investigation of criminal trials has determined the scientifically based directions in modern educational process of Latvia by training of specialists lawyers and, in particular, investigators. As a results of a research are given offers to change separate standards of the Criminal procedure law.